Um estudo do uso de padrões figurativos na aprendizagem de álgebra por alunos sem acuidade visual - Andrezzo, Karina Laguna (2005)
ABSTRACT This study aimed to identify factors that contribute to the understandings of algebraic expressions constructed by blind students. To this end, it involved the design of situations that would enable the participation of blind high-school students (Brazilian Ensino Médio) in generalizing activities. The research was inspired by Vygotsky s visions of the social integration and intellectual development of learners with special needs. The use of an approach to algebra emphasizing generalizations based on the patterns underlying sequences presented as spatial arrangements has been supported by various researchers in Mathematics Education, this study was informed particularly by the work of Küchemann (1981), Booth (1988) and Mason (1996). In the first phase of the research, materials based on the use of magnets to represent dynamic elements of sequences were designed and tested. The second phase involved five blind students in completing a preliminary activity, elaborated to obtain data about their performance on traditional algebra exercises followed by a series of interviews, during which each students worked through a set of seven generalizing activities. The analysis of the students responses to the preliminary activities indicated that the students had difficulties in dealing with three of six categories for interpreting letters in algebraic expressions described by Küchemann (1981), letter as specific unknown , letter as generalized number and letter as variable ; and identified errors committed during the simplification of expressions. Analysis of the interview data was based on the strategies the students used to construct mathematical generalizations. These analyses highlighted a process by which the external marks (the magnets and their organizations) were gradually internalized through the manipulations and articulations by which the learners strived to get a sense of algebraic expressions.